Chlamydia psittaci pneumonia in Wuxi, China: retrospective analysis of 55 cases and predictors of severe disease - Gao, Ying; Wu, Yan; Xu, Dan; Bao, Liang; Ding, Xiao; Lv, Lei; Ma, Chenhui; Bian, Tao; Han, Shuguang (Frontiers in Medicine, 2023)
More and more patients with community-acquired pneumonia have been detected with Chlamydia psittaci (C. psittaci) infected using metagenomic next-generation sequencing (mNGS). Previously, this was unheard of, and several patients presented with severe pneumonia and even required ECMO. We aimed to clarify the clinical characteristics of C. psittaci pneumonia and find out if there are any possible predictors of severe C. psittaci pneumonia.In this retrospective study, we included all confirmed cases of C. psittaci pneumonia in Wuxi. Epidemiological, clinical, and radiological features, as well as laboratory data, were collected and analyzed.We enrolled 55 patients with C. psittaci pneumonia, with 30 (54.5%) having a history of exposure to birds or their internal organs. 50 (90.9%) patients were diagnosed by mNGS. Patients with C. psittaci pneumonia had many complications, among which, that deserve sufficient attention from clinicians were vascular embolic events (3; 5.5%). High fever was the most common clinical manifestation (41; 74.5%).The majority of patients had a significant increase in neutrophils ratio, neutrophils to lymphocytes ratio (NLR), rapid c-reactive protein, creatine kinase (CK), and lactate dehydrogenase (LDH), as well as a decrease in lymphocytes ratio, albumin, serum sodium, serum potassium, and serum phosphorus. Chest computed tomography scans revealed unilateral pneumonia (70.9%), consolidation (87.3%), air bronchogram (76.4%), and ground-glass opacity (69.1%). The neutrophil ratio, NLR, LDH, and CK were all factors that could identify severe pneumonia. Both AUCs exceeded 0.8; the respective 95% CIs were 0.715 -0.944, 0.710 -0.963, 0.677 -0.937, and 0.718 -0.950; all P < 0.05 (0.01, 0.001, 0.007, 0.007 respectively). The ORs were 10.057, 9.750, 10.057, and 9.667, respectively; the 95% CIs were 2. 643 -38.276, 2.339 -40.649, and 2.643 -38.276, respectively; all P values were less than 0.05 (0.001, 0.002, 0.001, 0.001 respectively).Conclusions: Chlamydia psittaci pneumonia is a very complex disease that changes all the time. Some patients showed severe pneumonia. Patients will have a poor prognosis if they are not treated promptly and effectively. We discovered that many clinical indicators were typical. Meanwhile, significant increases in neutrophil ratio, NLR, LDH, and CK predicted severe pneumonia. Timely detection of mNGS provided substantial help for clinical diagnosis and early treatment.